Educational transfer as transformation : a case study about the emergence and implementation of dual apprenticeship structures in a German automotive transplant in the United States - Gessler, Michael [Verfasser] (My University, 2017)
"The apprenticeship system in Germany is carried out both by companies and vocational schools (the Dual System). The question of whether the German Dual System is transferable is currently being asked in vocational education and training research. The analysis of current transfer discourses alludes to a research desideratum: the actual approaches consider either the input or the output of an educational transfer, but the transfer process in relation to its input and output has not been investigated to date. We focus on this desideratum. In the present case study, the processes emergence and implementation of dual apprenticeship structures is analysed in relation to its input and output in a German automotive transplant in the United States. Transplant organisations provide an ideal case to explore the transfer phenomenon because they have been transferred from a familiar context to a foreign context. The research questions are: firstly, why and how did the need emerge to implement dual apprenticeship structures in the German transplant in the United States (input); secondly, how and in which way have these structures been implemented (process); and thirdly, how can the implemented structures be characterised: as an imitation, adaptation or transformation of the original model (output)? The central findings of the case study are: firstly, that growing contradictions in the production system triggered the implementation process; secondly, that the original Dual System was transformed within the implementation process; and thirdly, that this transformation led to innovative solutions. These findings may not be valid for every transfer at any time, but they reflect that educational transfer of dual apprenticeship structures can be more than just a more or less successful imitation or adaptation." (Authors' abstract, BIBB-Doku)
OnlineFirst am 14.7.2016
Keywords: S 1.3.1 Ausbildung im Dualen System; I 1 Internationale Berufsbildung; G 1.2.4.1 Produktion und Gewinnung; I 2.3.2 Nordamerika; Duales System; Transfer; Internationale Zusammenarbeit; Automobilindustrie; USA